PENERAPAN MODEL QUANTUM TEACHING DAN METODE SNOWBALL THROWING MELALUI KOLABORASI TERHADAP MINAT DAN PRESTASI BELAJAR KIMIA (Pokok Bahasan: Tata Nama Senyawa Serta Persamaan Reaksinya Pada Siswa Kelas X SMA Negeri 4 Jayapura) - Manrudda, Munawwarah; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2013)
This study aims to analyze the application of quantum teaching learning models and methods of snowball throwing through the collaboration of the chemical of interest and achievement (subject: compound nomenclature and equation in class X SMAN 4 Jayapura). The method used in this study was quasi experimental with a sample of 100 people were divided into two classes (class control and experimental classes). The results reveal that there are different interests and student achievement between the classes that use quantum model of learning and teaching through collaboration throwing snowball method used class of models than conventional learning, evidenced through Asymp value. Sig. (2-tailed) of 0.000 resulting from the Mann Whitney U test In addition there is a difference of understanding the concept of students as evidenced from the average normalized gain overall grade of 0.80 compared to classroom experiments using conventional learning models of 0.35. Keywords: Quantum Teaching, Snowball Throwing, Interests Learning and Learning Achievement